The mature personality of the heads of departments and its relationship to the abundance of experience they have from the point of view of the teachers (Journal of the College of Basic Education, 2023)
Universities represent one of the important institutions for any society that seeks progress and works to have its place, includingProvides efforts to the community in raising generations and preparing specialists in various fields of science and knowledgeAl-Hamid et al. 2007} 81) This broad concept includes a person's characteristics, abilities, and motivationsAnd his mood, his performance, his beliefs, his emotions, his cognitive pattern, and the moral aspect of his behavior, leading to the fact that he representsThe total sum of the behavior issued by the person (1984,215